Thiolate photocatalysis enables radical borylation of reductively inert aryl electrophiles - Li, Haoyu (2022)
The facile installation of functionalities to aromatic compounds via chemical activation of inert carbon-heteroatom bonds is a challenging task. In this issue of Chem, König and co-workers disclose a photocatalytic protocol for the radical borylation of reductively inert aryl electrophiles, such as aryl fluorides and aryl carbonates, by using simple thiolate salts as a catalyst.